Lo soldadesco en la poesía de Héctor Viel Temperley: amor, ideales y masculinidad factibles - Arancet Ruda, María Amelia (2023)
According to critics, Viel Temperley is an Argentine mystical poet, but here we address a different facet, operative in relation to subjective representation and the encoding of a worldview: the iteration of military figurations, especially those of the soldier and its variants, in texts, paratexts and epitexts the latter, crucial in this work to validate the explored inclination, also supported by extraliterary documents. There is a multivocal repertoire of soldiery themes, deeply rooted in Argentine history and, furthermore, associated with the masculine imaginary of a particular era. This repertoire constructs the masculine self, but according to a subverted and destabilizing version, which ranges from love to heroism, even to the freedom of poetry. Due to this anti-system dissent, the figure of Juan Lavalle, dear to our author, is a kind of double in several compositions, and it sheds light on some of the meanings that soldiery acquires in Viel’s work.